Attention Problems in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
The relation of laterality of the epileptogenic focus to cognition and attention in 43 unmedicated children, mean age 10 years, with benign rolandic epilepsy of childhood was assessed at Clinica Neurologica Universita, Perugia, Italy.